ANALISIS FAKTOR YANG MEMENGARUHI NILAI PERUSAHAAN MANUFAKTUR PERIODE 2017-2019 - Nathalia Angeline; Lie Sha Thio (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This research’s goal is to get empirical evidence of the effect of sales growth, firm size, liquidityand sales growth on firm value. The sample that used in this study are manufacturing companieslisted on the IDX in 2017-2019. This research uses purposive sampling where the sample selectedwas 33 companies. Data processing with multiple regression analysis with Eviews 12 andmicrosoft excel. The results showed that firm size has a negative and significant effect on firmvalue. While leverage, liquidity and sales growth has insignificant effect on firm value. Theimplication of this research is that a company need professional and competent management toassist the company in improving their firm value so that the company can compete in the industry.